The Damaged Spinal Cord Is a Suitable Target for Stem Cell Transplantation. (August 2020) - Curt, Armin; Hsieh, Jane; Schubert, Martin; Hupp, Markus; Friedl, Susanne; Freund, Patrick; Huber, Evenline; Pfyffer, Dario; Sutter, Reto; Jutzeler, Catherine; Wüthrich, Rudolf P.; Min, Kan; et al.
Background . Given individuals with spinal cord injury (SCI) approaching 2 million, viable options for regenerative repair are desperately needed. Human central nervous system stem cells (HuCNS-SC) are self-renewing, multipotent adult stem cells that engraft, migrate, and differentiate in appropriate regions in multiple animal models of injured brain and spinal cord. Preclinical improved SCI locomotor function provided rationale for the first-in-human SCI clinical trial of HuCNS-SC cells. Evidence of feasibility and long-term safety of cell transplantation into damaged human cord is needed to foster translational progression of cellular therapies. Methods . A first-ever, multisite phase I/IIa trial involving surgical transplantation of 20 million HuCNS-SC cells into the thoracic cord in 12 AIS A or B subjects (traumatic, T2-T11 motor-complete, sensory-incomplete), aged 19 to 53 years, demonstrated safety and preliminary efficacy. Six-year follow-up data were collected (sensory thresholds and neuroimaging augmenting clinical assessments). Findings . The study revealed short- and long-term surgical and medical safety (well-tolerated immunosuppression in population susceptible to infections). Preliminary efficacy measures identified 5/12 with reliable sensory improvements. Unfortunately, without thoracic muscles available for manual muscle examination, thoracic motor changes could not be measured. Lower limb motor scores did not change during the study. Cervical cord imaging revealed, no tumor formation or malformation of the lesion area, and secondary supralesional structural changes similar to SCI control subjects. Interpretation . Short- and long-term safety and feasibility support the consideration of cell transplantation for patients with complete and incomplete SCI. This report is an important step to prepare, foster, and maintain the therapeutic development of cell transplantation for human SCI.